Визначення закономірностей оцінок показників якості технологічного процесу на безрозмірній шкалі - Кім, Н. І.; Kim, N. (ЦНТУ, 2021)
В статті визначено головні умови до кількості і якості статистичної інформації для управління якістю технологічного процесу. Показано, що правильність і ефективність вирішення практичних завдань, застосовуючи статистичні методи оцінювання якості, визначається обсягом інформації про функціонування технологічного процесу. Представлено результати дослідження, пов'язані з визначенням закономірностей розподілу оцінок показників якості технологічного процесу на безрозмірній шкалі. The purpose of the article is to study the patterns of evaluation of quality indicators of the technological process on a sizeless scale. The quality of production depends on the quality of technological processes, namely - many factors of technological, technical and organizational nature. The technological process is the basis of any production process, is the most important part of it, associated with the processing of raw materials and its transformation into finished products. Product quality is the most important indicator of companies seeking to develop and succeed in competition among other manufacturers. This issue is especially relevant for Ukrainian companies seeking to be competitive in the European and world markets. To manage the quality of the object often have to use statistical methods of evaluation and management, where, as basic information you need to know not the law of distribution of quality in its units, and know the law of distribution of their assessments on a sizeless scale, therefore, research related to determining the patterns of distribution of assessments of quality indicators of the technological process on a sizeless scale. Knowing the law of distribution of unit quality indicators of the object of qualimetry and knowing the dependence with their estimates on a sizeless scale, it is possible to solve practical problems to determine the probability of getting estimates of quality indicators in a given interval. The solution of such problems is relevant in determining the risks of the processes of quality management systems, or determining the reliability of the technological process and other indicators. As a result of the study, the main conditions for the quantity and quality of statistical information were identified. It is shown that the correctness and efficiency of solving practical problems, using statistical methods of quality assessment, is determined by the amount of information about the functioning of the technological process, which can be divided into conservative and operational. Conservative information includes knowledge of the distribution law and finding effective statistical estimates of its parameters, and operational – the sample size.
Determining of Regularities of Evaluations of Technological Process Quality Indicators on a Sizeless Scale
Keywords: об’єкти кваліметрії; технологічний процес; статистичний аналіз; функції щільності; безрозмірна шкала; узагальнений показник якості; qualimetry objects; technological process; statistical analysis; density function; sizeless scale; generalized quality indicator